Bursting Your Balloon: Examining Differences in Self-Other Decision Making Using the BART Task - Guðrún Carstensdóttir 1991- (2015)
Making risky decisions for oneself and the role affect play in that process has been extensively studied. In contrast however, little is known about the process of risky decision making on behalf of others. This thesis explores risky decision making, whether making risky decisions for others differs from making them for oneself, and if so how. Furthermore, it examines if positive and negative affect differentially affect decision making for others versus oneself. Participants were 37 undergraduate psychology students. Age ranged from 21 to 38 years (M = 24.46, SD =3.83), 32 were female and 5 were male. Participants were randomly assigned conditions. They either had to make decisions for themselves or to make decisions for a nonspecific family member. Decisions were measured using the BART task and positive and negative affect was assessed with the PANAS scale. The results showed that there was no difference between groups regarding decision making. Positive affect was associated with increased risk but negative affect was unrelated to risky decision making. Finally, affect did not differentially affect decision making for others versus oneself. Future studies should use a more holistic approach to further our understanding of decision making as a whole. Áhrif tilfinninga á ákvarðanatöku hefur verið vel rannsakað á undanförnum árum og áratugum. Ákvarðanataka hefur í flestum tilvikum verið rannsökuð með einstaklingin í huga og ákvarðanir er varða hann sjálfan en það hvernig einstaklingur tekur ákvarðanir fyrir aðra hefur lítið verið rannsakað. Tilgangur þessarar rannsóknar er því að skoða hvort áhættusamar ákvarðanir eru ólíkar eftir því hvort að ákvörðun er tekin fyrir sjálfan sig eða fyrir einhvern annan. Einnig er kannað hvort tilfinningar hafi ólík áhrif á þessar tvær tegundir ákvarðanatöku. Þátttakendur voru 37 grunnnemar í sálfræði við Háskólann í Reykjavík. Aldur þátttakenda var á bilinu 21 til 38 ár (M = 24.46, SD =3.83) og af þeim 37 nemendum sem tóku þátt voru 32 konur og 5 karlar. Þátttakendum var ...